2020
DOI: 10.1111/jonm.13144
|View full text |Cite
|
Sign up to set email alerts
|

Nursing turnover intentions: The role of leader emotional intelligence and team culture

Abstract: Aim To explore the influence of leader emotional intelligence on the working culture prevailing in teams that ultimately impacts nurses’ intent to leave the job. Background Global shortages of nursing professionals have been concerning issues of extreme vitality in the delivery of superior services. Though the state‐of‐the‐art system provides relief, the hospital management continued worrying about losing highly skilled nursing professionals due to a higher level of emotional exhaustion exhibiting progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…In high-resourced settings, though RNs' turnover intentions are low, the lack of leadership support, inadequate involvement of RNs in hospital affairs, and material and human resource constraints at the workplace are observed to be predictors of RNs' turnover intention. Again, nurses' emotional exhaustion and perception of job engagement are significant mediators of nurses' turnover intentions in an organization [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In high-resourced settings, though RNs' turnover intentions are low, the lack of leadership support, inadequate involvement of RNs in hospital affairs, and material and human resource constraints at the workplace are observed to be predictors of RNs' turnover intention. Again, nurses' emotional exhaustion and perception of job engagement are significant mediators of nurses' turnover intentions in an organization [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a finding of concern given the great importance of EI in the practice of nursing that may influence their performance and wellbeing at work, and consequently their continuance in the nursing career. In fact, research has demonstrated that the nurses having low EI were more likely to leave their jobs (Majeed and Jamshed, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A constructive team culture has, for example, a positive impact on person‐centred care [ 26 , 27 ] and team members’ perceptions of empowerment [ 28 ]. It also helps to prevent adverse events [ 29 ], reduce staff turnover [ 30 ] and promote job satisfaction and quality in care [ 24 ]. Nurses’ experiences of handling acute care challenges are found to be associated with a professional and positive team culture and interprofessional collaboration [ 31 ].…”
Section: Team Culture and Competence Planningmentioning
confidence: 99%